Rancang Bangun Alat Thermohygrometer Dilengkapi Sensor Pemantauan Gas Medik - Junior Yudha Pamungkas; Weni Hastuti; Setyo Adi Nugroho; Eko Nugroho (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
Thermohygrometer is a tool that functions to measure room temperature and humidity. The temperature and humidity in the operating room are set in the temperature range of 19˚C - 24˚C and humidity of 45% - 65%. Therefore, the operating room requires a good temperature and humidity control system to avoid damage to electronic components due to temperatures that are too low and humidity that is too high which causes corrosion. In addition, the influence of high concentrations of medical gas accelerates the rate of corrosion. Because medical gas consisting of CO and CO₂ gas contains oxygen as an oxidant gas. Therefore, a tool such as a Thermohygrometer is needed but equipped with a medical gas reading. This tool aims to read the conditions of temperature, humidity, and medical gas (CO & CO₂) so that it can be analyzed by Electromedics to regulate the air conditioning system. In addition, a Thermohygrometer system is made to allow data access from outside the operating room. The Thermhygrometer tool is made using two sensors, namely DHT22 and MQ-135. DHT22 is used to read temperature and humidity parameters, while the MQ-135 sensor is used to read the concentration of CO and CO₂ gases. The reading results are displayed on the I2C LCD screen. The components are integrated with ESP32 for data processing and as hardware that can be used to create a WiFi connection system. WiFi connectivity is needed to send data to the Blynk application. Testing by calibrating the DHT22 sensor and testing the suitability of the MQ-135 sensor with the gas analyzer. Based on the tests carried out, the temperature error value was obtained at -0.02% and humidity at -0.02%. While the error value was 0.32% for CO gas and -0.16% for CO₂ gas. The error value is still within the tolerance limit